2017
DOI: 10.1007/s10661-017-5977-4
|View full text |Cite
|
Sign up to set email alerts
|

Preferential flow characteristics of reclaimed mine soils in a surface coal mine dump

Abstract: There are a large number of macropores/tubular channels of a few centimeters and plant roots in reclaimed dump soils, which are the main reasons for the formation of soil macropores and soil preferential flow. To systematically study the morphological characteristics and variation of soil preferential flow for different reclaimed vegetations in a dump, a dye-staining experiment and physical and chemical analysis were carried out to investigate the formation mechanism and influencing factors of soil preferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Under the combined action of gravity potential and solute potential, the outflow speed with higher influent concentration was accelerated, the peak value was higher, and the time to complete the outflow is shorter. Gang et al (2017) showed that the earlier initial penetration was also one of the characteristics of soil preferential flow [10] . Under the same conditions, with the increase of influent concentration, the outflow velocity rate of soil sample water became faster, and the time to complete the outflow was shorter, the phenomenon of solute preferential flow was more obvious (Table 1).…”
Section: Effects Of Different Influent Concentrations On No3-n Preferential Transportmentioning
confidence: 99%
“…Under the combined action of gravity potential and solute potential, the outflow speed with higher influent concentration was accelerated, the peak value was higher, and the time to complete the outflow is shorter. Gang et al (2017) showed that the earlier initial penetration was also one of the characteristics of soil preferential flow [10] . Under the same conditions, with the increase of influent concentration, the outflow velocity rate of soil sample water became faster, and the time to complete the outflow was shorter, the phenomenon of solute preferential flow was more obvious (Table 1).…”
Section: Effects Of Different Influent Concentrations On No3-n Preferential Transportmentioning
confidence: 99%